Effects of transcutaneous neuromuscular electrical stimulation on post-stroke dysphagia: a systematic review and meta-analysis - Wang, Yuhan; Xu, Lu; Wang, Linjia; Jiang, Minjiao; Zhao, Ling (Frontiers in Neurology, 2023)
Background Dysphagia is one of the common complications after stroke. It is closely related to lung infection and malnutrition. Neuromuscular electrical stimulation (NMES) is widely used in the treatment of post-stroke dysphagia, but the evidence-based medical evidence of NMES is limited. Therefore, this study aimed to evaluate the clinical efficacy of NMES in patients with post-stroke dysphagia by systematic review and meta-analysis. Methods We searched the CNKI, Wanfang, VIP, SinoMed, PubMed, Embase, Cochrane Library, and Web of Science databases for all randomized controlled trials (RCTs) of NMES in the treatment of post-stroke dysphagia from the establishment of the database to 9 June 2022. The risk of bias assessment tool recommended by Cochrane and the GRADE method was used to assess the risk of bias and the quality of evidence. RevMan 5.3 was used for statistical analysis. Sensitivity and subgroup analyses were performed to evaluate the intervention effect more specifically. Results A total of 46 RCTs and 3,346 patients with post-stroke dysphagia were included in this study. Our meta-analysis showed that NMES combined with routine swallowing therapy (ST) could effectively improve swallowing function in Penetration-Aspiration Scale (MD = −0.63, 95% CI [−1.15, −0.12], P = 0.01), Functional Oral Intake Scale (MD = 1.32, 95% CI [0.81, 1.83], P < 0.00001), Functional Dysphagia Scale (MD = − 8.81, 95% CI [−16.48, −1.15], P = 0.02), the Standardized Swallowing Assessment (MD = −6.39, 95% CI [−6.56, −6.22], P < 0.00001), the Videofluoroscopic Swallow Study (MD = 1.42, 95% CI [1.28, 1.57], P < 0.00001) and the Water swallow test (MD = −0.78, 95% CI [−0.84, −0.73], P < 0.00001). Furthermore, it could improve the quality of life (MD = 11.90, 95% CI [11.10, 12.70], P < 0.00001), increase the upward movement distance of hyoid bone (MD = 2.84, 95% CI [2.28, 3.40], P < 0.00001) and the forward movement distance of hyoid bone (MD = 4.28, 95% CI [3.93, 4.64], P < 0.00001), reduce the rate of complications (OR = 0.37, 95%CI [0.24, 0.57], P < 0.00001). Subgroup analyses showed that NMES+ST was more effective at 25 Hz, 7 mA or 0–15 mA, and at courses ( ≤ 4 weeks). Moreover, patients with an onset of fewer than 20 days and those older than 60 years appear to have more positive effects after treatment. Conclusion NMES combined with ST could effectively increase the forward and upward movement distance of the hyoid bone, improve the quality of life, reduce the rate of complications, and improve the swallowing function of patients with post-stroke dysphagia. However, its safety needs to be further confirmed. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier: CRD42022368416.